Synthesis, Thermal, Structural Analyses, and Photoluminescent Properties of a New Family of Malonate-Containing Lanthanide(III) Coordination Polymers - Hussain, Sajjad; Chen, Xuenian; Harrison, William T. A.; Ahmad, Saeed; Elsegood, Mark R. J.; Khan, Islam Ullah; Muhammad, Shabbir (Frontiers in Chemistry, 2019)
Five new Lanthanide(III) complexes of malonic acid (HOOC-CH2-COOH); {[Gd(C3H2O4)(H2O)4]•NO3}n (1), {[Tb(C3H2O4)(H2O)4]•NO3}n (2),{[Ho(C3H2O4)(H2O)4]•NO3}n (3), [Er(C3H2O4)(C3H3O4)(H2O)2]n (4) and {[Eu2(C3H2O4)2(C3H3O4)2(H2O)6]•4H2O}n (5) are synthesized and characterized by elemental, infrared spectral and thermal analyses. The structures of compounds 1-5 are determined by single crystal X-ray diffraction technique. The X-ray analysis reveals that compounds 1, 2 and 3 are isostructural and crystallized in the orthorhombic space group Pmn21. The lanthanide(III) ions are coordinated by four carboxylate and four water oxygen atoms adopting a distorted square antiprism geometry. The LnO8 square antiprisms are linked into infinite layers by malonate (C3H2O42–) dianions sandwiching sheets of nitrate counter ions. Compound 4 contains ErO8 square antiprisms linked into a two-dimensional network by hydrogen malonate (C3H3O4–) anions and malonate dianions. The europium complex, 5 is dinuclear having the two europium(III) ions (Eu1 and Eu2) bridged by carboxylate groups of hydrogen malonate ligands. The europium ions in 5 are nine-coordinate and exhibit a distorted monocapped square antiprism geometry. All the structures are consolidated by O–H∙∙∙O hydrogen bonds. The photoluminescence spectra of 1-5 exhibit characteristics emission in the visible region. The IR spectra and thermal data are consistent with the structural results. The room-temperature effective magnetic moments for 1–4 are in good agreement with those expected for the free ions, while the data for 5 indicates that low-lying excited states contribute to the observed moment. The compound 1 was further subjected to quantum computational calculations to explore its optoelectronic properties including; density of states (DOS), dielectric function, refractive index, extinction coefficient and absorption spectrum, to highlight the possible applications of such materials in the optoelectronics.